Clinicoradiographic evaluation of different intracoronal and extracoronal restorative materials for the restoration of carious primary molars: a twelve month follow-up study - Kaul, Sampada; Srivastava, Nikhil; Rana, Vivek; Kaushik, Noopur (International Journal Of Community Medicine And Public Health, 2022)
Background: To assess clinical and radiographic efficacy of conventional GIC, stainless steel crown (HT), and Alkasite restoration (Cention N) as management options for cavitated primary molars and to evaluate their success clinico-radiographically in terms of survival, patient’s acceptance and parental satisfaction over a minimum period of 12 months. Methods: IOPAs were taken to assess the extent of caries. Cavitated primary teeth were subjected to following procedures randomly: GROUP I- (GIC) - Isolation followed by soft caries removal, then restoration of cavity with GIC. Patient recalled after 24 hours for finishing and polishing of restoration. GROUP II- (SSC) - Proper isolation followed by soft caries removal. Appropriately sized prefabricated SSC fit and cemented by luting GIC. GROUP III- (AK) - Isolation followed by soft caries removal, restoration of cavity with Alkasite and light cured for setting and finished. Results: In terms of pain, secondary caries and pulpal involvement, 10% cases failed in group I and group III while 100% success was seen in group II. In terms of longevity, maximum dislodgement was seen in group I (30%) followed by group III (10%) while 100% success was seen in group II. In terms of patient and parent acceptance, group III was most widely accepted by patients at baseline while parents were satisfied with group II at the end of the study. Conclusions: All restorative materials were clinically and radiographically successful in restoration of primary molars in terms of survival, patient acceptance and parental satisfaction, however Stainless-Steel crowns proved to be most efficacious.